Approaches to the stabilization of bioactive epitopes by grafting and peptide cyclization. Issue 1 (January 2016) - Conibear, Anne C.; Chaousis, Stephanie; Durek, Thomas; Johan Rosengren, K.; Craik, David J.; Schroeder, Christina I.
ABSTRACT: Peptides are attracting increasing interest from the pharmaceutical industry because of their specificity and ability to address novel targets, including protein–protein interactions. However, typically they require stabilization for therapeutic applications owing to their susceptibility to degradation by proteases. Advances in the ability to chemically synthesize peptides and the development of new side‐chain and backbone ligation strategies provide new tools to stabilize bioactive peptide epitopes. Two such epitopes are LyP1, a nine residue peptide that localizes to tumor cells and has potential as an anticancer therapeutic, and RGDS, a tetrapeptide shown to bind to survivin and induce apoptosis. Here we applied a variety of strategies for the stabilization of LyP1 and RGDS, including side‐chain cyclization using "click" chemistry and "grafting" the epitopes into two naturally occurring cyclic peptide scaffolds, i.e., θ‐defensins and cyclotides. NMR data showed that the three‐disulfide θ‐defensin and cyclotide scaffolds accommodated the LyP1 and RGDS epitopes but that scaffolds with fewer disulfide bonds were structurally compromised by inclusion of the LyP1 epitope. LyP1, LyP1‐, and RGDS‐grafted peptides that were largely unstructured also had reduced resistance to degradation in human serum, showing that grafting into a stable cyclic scaffold is an effective strategy for increasing the stability of a bioactive peptide epitope. Overall, the study demonstrates several methods for stabilizing peptide epitopes using side‐chain or backbone cyclization and illustrates their potential in peptide drug design. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 89–100, 2016.